Crimean-Congo Hemorrhagic Fever (CCHF): Our Experience at a Tertiary Hospital - Khan, Zubair Waheed; Ali, Gulzar; Ahmed, AKhlaq; Tariq, Muhammad; Gardezi, Adeel; Khan, Nauman Sarir (Pakistan Armed Forces Medical Journal, 2022)
Objective: To share our experience of managing Crimean-Congo Hemorrhagic Fever cases at tertiary care hospital. Study Design: Hospital based case series. Place and Duration of study: Medicine department Combined Military Hospital Peshawar, from 2017 to 2019. Methodology: A total of 10RT-PCR positive cases of Crimean-Congo Hemorrhagic Fever were included in the study. Data were collected retrospectively from Stat office of the hospital. All cases which were PCR negative, having multiple co-morbid conditions and having alternative diagnoses were excluded from the study. Demographic, epidemiological, clinical and laboratory parameters were noted on a specially designed Proforma. Results: All patients were males armed forces personnel employed in the tribal areas of KPK. All patients initially developed fever and generalized body pains. Among them 2 (20%) patients developed petechial rash and 1(10%) suffered from epistaxis, melena and hematuria. All (100%) of the patients’ lab data revealed leukopenia, thrombocytopenia, elevated ALT and LDH. Complete recovery was noted in all patients. 8 (80%) of the patients received ribavirin and platelet transfusion. All patients under study also received oral Vitamin C supplement. Average hospital stay was 14 days. Conclusion: Crimean-Congo Hemorrhagic Fever is a fatal disease. People visiting to endemic areas are at particular risk such as soldiers. It is manifested by fever, petechial rash and thrombocytopenia. Treatment is supportive. The role of oral vitamin C supplements and ribavirin to hasten recovery needs further high-powerstudies andshould be given to all suspected and confirmed cases.